A Self-Adhesive Serpentine based Passive UWB tag for Wireless Medical Data Monitoring - Prakash, Stephen; John, Tanya Saira; Samuelraj Chrysolite, G (2025 International Conference on Wireless Communications Signal Processing and Networking (WiSPNET), 2025)
Medical data verification has become a notable challenge in the post-COVID era. Various technologies such as Wi-Fi, Bluetooth, RFID, ZigBee, etc., are widely used for monitoring and transmission of data in the healthcare environment. These technologies pose certain limitations through their high power consumption and large devices. Hence a novel wearable, flexible and adhesive antenna design that uses passive Ultra-Wideband (UWB) tagging, to store and transmit medical information is proposed. A UWB tag requires less power and is a compact system compared to other technologies. The proposed antenna with dimensions 10 x 10 x 0.06 mm3 comprises of a polyimide substrate and a copper radiating patch. The antenna performance is simulated for parameters like voltage standing wave ratio, reflection coefficient, radiation pattern (2-D and 3-D) and Specific Absorption Rate (SAR) on a three-layer homogeneous system. Unlike other approaches to transmit data through UWB, this method uses UWB that operates at 7.2 Giga Hertz (GHz) to avoid interferences that are usually seen at 5 GHz. Specific absorption rate for 10 gram of tissue is measured to be 1.526 W/kg for an input power of 1.8 milli Watts (mW), marking this as a safer approach for human use. Reflection coefficient of −49.99 decibel (dB) with a good impedance matching of 49.04 Ω is achieved. Measured results are analysed for the proposed fabricated antenna by worn on the hands of a live subject. Accessing wearable antenna-stored data involves a UWB reader emitting high-power radio pulses across frequencies intercepted by antenna tag with passive Ultra-Wideband (UWB). Hence the proposed wearable antenna offers a solution for storing and monitoring important medical information like reverse transcriptase-polymerase chain reaction (RT-PCR) in real-time for a huge gathering thereby reducing verification time.